Anatomic landmarks and availability of bone for placement of orthodontic mini-implants for normal and short maxillary body lengths - Hourfar, Jan; Lux, Christopher J. (American journal of orthodontics and dentofacial orthopedics, 2017)
Introduction: Increasing numbers of orthodontic mini-implants are placed in the anterior maxilla. To our knowledge, bone levels and root proximity of patients with cephalometrically short maxillae have not been investigated before. The first, second, and third rugae were used as clinical reference lines, and the aim of this study was to measure bone availability in that area by comparing patients with short and normal maxillary body lengths. Methods: The sample consisted of 21 patients in each group: short maxillary body length and normal maxillary body length. The patients’ study models were bisected, and the outline of the palatal contour was marked on the surface. The models were scanned, and the palatal contours were superimposed on the palatal structures of their respective initial cephalometric headfilms, and the vertical and oblique bone levels of the sagittal plane were compared using the Student t test. The level of significance was set at P <0.05. Results: Compared with maxillae of normal maxillary body length, less bone was available in maxillae of short maxillary body length. However, the differences did not reach clinical or statistical significance (P >0.05) at the third rugae. Conclusions: Almost equivalent average bone depth at the third rugae in patients with normal and short maxillary body lengths suggests that this site can be used for 8-mm long obliquely inserted orthodontic mini-implants.